The Europeanisation of board-level employee representation in France: An emerging role for European Works Councils? - Sara Lafuente (European Trade Union Institute (ETUI), 2022)
In France, the legal obligation for private-sector companies to have, under certain conditions, one or two employee representatives on their boards goes hand in hand with the possibility for the company to decide to have its European Works Council (EWC) or SE Works Council (SE-WC) appoint the second member. This has become the preferred option for French companies. As the recent PACTE Law ('loi 'Plan d'Action pour la Croissance et la Transformation des Entreprises') has lowered the board-size threshold obliging companies to have two employee representatives on their boards, it is expected that the number of companies affected will increase, and consequently, that of members appointed by EWCs or SE-WCs. This emerging Europeanisation brings opportunities but also legal and political uncertainties for the board-level employee representation (BLER) system in France, and for newly appointed board-level employee representatives, especially when these are non-French*, which is now de facto a possibility. EWCs and SE-WCs have generally not anticipated or addressed this issue in their agreements. Although internal rules of procedures have sometimes addressed practical problems, given the limited normative power of this instrument, this is clearly insufficient. National and European legislative action needs to focus on securing more democratic and transparent processes and adequate protections for representatives assuming European mandates.
Keywords: 330; board-level employee representation; Europeanisation; European Works Councils; French multinationals; PACTE Law